Discretization of skew slabs - Yu, Ming-hong; Tongchat Hongladaromp; Lee, Seng-Lip; Government of the Republic of China (Bangkok : Asian Institute of Technology, 1973)
The analysis of equivalent grid framework representing skew slabs in flexure is investigated. An orthogonal grid model with one series of the orthogonal grid members normal to supported edges is used to discretize skew slabs with uniform thickness. The stiffness method of structural analysis is employed to analyze the grid system. Four cases of skew slabs with different boundary conditions are investigated to show how orthogonal discretization can be used for the analysis of the skew slabs and how to simulate the boundary conditions. A detailed comparison of deflections, moments and torques predicted by the equivalent grid framework system is given for different types of skew slab. The results obtained from the analysis of equivalent grid framework are found to be in good agreement with those obtained by other methods, notably the finite difference and the finite element methods, except for results obtained along free edges. Proper simulation of boundary conditions and good engineering judgement must be exercised in utilizing this method for the purposes of practical design.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand.
Thesis (M.Eng.) - Asian Institute of Technology, 1973
Keywords: Slabs; Plates (Engineering)